The Role of Macrophages During Zebrafish Injury and Tissue Regeneration Under Infectious and Non-Infectious Conditions - Bohaud, Candice; Johansen, Matt D.; Jorgensen, Christian; Ipseiz, Natacha; Kremer, Laurent; Djouad, Farida (Frontiers in Immunology, 2021)
The future of regenerative medicine relies on our understanding of the mechanistic processes that underlie tissue regeneration, which rely on suitable animal models. For many years, the zebrafish has been exploited as an adequate model in the field due to its very high regenerative capabilities. In this organism, regeneration of several tissues, including the caudal fin, is dependent on a robust epimorphic regenerative process, typified by the formation of a blastema, consisting of highly proliferative cells that can regenerate and completely grow the lost limb within a few days. Recent studies have also emphasized the crucial role of distinct macrophage subpopulations in tissue regeneration, contributing to the early phases of inflammation and promoting tissue repair and regeneration in late stages once inflammation is resolved. However, while most studies were conducted under non-infectious conditions, this situation does not necessarily reflect all the complexity of the interactions associated with injury often involving entry of pathogenic microorganisms. There is emerging evidence that the presence of infectious pathogens can largely influence and modulate the host immune response and the regenerative processes, which is sometimes more representative of the true complexities underlying regenerative mechanics. Herein, we present the current knowledge regarding the paths involved in the repair of non-infected and infected wounds using the zebrafish model.